"We Look (and Feel) Better Through System-Justifying Lenses": System-Justifying Beliefs Attenuate the Well-Being Gap Between the Advantaged and Disadvantaged by Reducing Perceptions of Discrimination. (September 2019) - Bahamondes, Joaquín; Sibley, Chris G.; Osborne, Danny
Low-status groups report lower levels of well-being than do high-status groups. Although system justification theory posits that the endorsement of system-justifying beliefs should decrease this well-being gap, the underlying mechanisms responsible for this hypothesized palliative effect have evaded empirical scrutiny. We address this oversight by arguing that system-justifying beliefs confer palliative benefits upon low-status groups by decreasing perceptions of group-based discrimination. Using nationally representative data from New Zealand ( N = 12, 959), we demonstrate that ethnic minorities (Study 1a) and women (Study 1b) generally report lower levels of well-being than do New Zealand Europeans and men, respectively. Nevertheless, as hypothesized, these differences were mitigated by the endorsement of ethnic- and gender-specific system justification, respectively. Mediated moderation analyses further revealed that part of the palliative effects of system justification occurred via reductions in perceived group-based discrimination. The implications of these findings for intergroup relations are discussed.